Minor emergencies - Buttaravoli, Philip M. (Elsevier/Saunders, 2012)
Whether you're called on to remove a bean from a child's nose or treat accidental tear gas exposure, this title provides the instructions you need to handle common, non-life-threatening emergencies with speed and expertise.